The intersection of social class with race and gender: transitioning to first-time managers in professional firms - Rossouw, Christine (Graduate School of Business (GSB), 2026)
The transition to managerial roles is a defining moment in professional trajectories, yet it presents unique challenges shaped by individuals' identities. Despite the growing recognition of diversity in the workplace, social class remains an underexplored dimension that profoundly influences professional workplace experiences. Social class context impacts access to resources and opportunities, shaping workplace behaviours and interactions. This study examines how social class, intersecting with race and gender, influences the experiences of first-time managers (FTMs) navigating new roles. Set within the context of South Africa, where historical and socio-economic disparities persist, the research focuses on professional workplaces as a compelling site for exploring upward leadership mobility. Using an interpretive phenomenological approach, the study gathers longitudinal insights from 13 managers at a national audit and accounting firm in 2023 over nine to eleven months. The findings reveal that social class informs behaviours critical to transitioning, such as learning agility, self-advocacy, and building relationships, while intersecting with race and gender to amplify challenges and opportunities. By amplifying diverse voices and highlighting the nuanced impact of intersecting identities on managerial transitions, this study provides novel insights into the interplay of identity, managerial success and the role of social class in organisations. It advances understanding of managerial transitions while offering practical implications for leadership development and organisational inclusivity, supporting diverse talent in their progression to managerial roles.